Early Breast-Feeding Initiation Using Point of Care Quality Improvement Model at Tertiary Care Hospital in AJK - Khan, Aftab Hussain; Khan, Mumtaz Ahmed; Akbar, Abrar; Mumtaz, Sehrish; Abbasi, Yasira; Meraj, Lubna (Journal of Rawalpindi Medical College, 2023)
ABSTRACT: Urgency and solely utility of breast feeding for six months is better for the provision of a healthy start to newborn and reduces infant mortality and morbidity. The prevalence of late lactation and other ways to formula or animal milk feeding the neonate in Pakistan is often observed other than the WHO recommendations. Early initiation of breast feeding is one of the indicators to express quality of Care in Maternal, and newborn Health. Among many approaches, point of care Quality improvement initiative (POCQI) is a simplified tool for learning the basics of quality improvement in the health care facilities. This study aimed to assess the prevalence and associated factors of early initiation of breastfeeding among mothers in a tertiary care hospital in AJK, where POCQI has been piloted. Methods: A quality improvement, cross sectional study before and after the implementation of POCQI model on two independent samples was carried out from August to November 2019. A total of 100 women (50 before intervention and 50 after intervention) who delivered neonates of 0-7 day’s age were included in study by using non-probability convenience sampling technique. The relevant information was gathered by using questionnaire. Mothers who did not start breast feeding within first hour did not receive any health education during antenatal visits. such women lack knowledge about benefits of colostrum. Hence an intervention was introduced by Researcher jointly in collaboration with POCQI team of the hospital by using Plan-Do-Study-Act (PDSA) cycle. Slogans and health education messages for promotion of early initiation of breast feeding were developed and message was spread to pregnant mothers who visited hospital for antenatal care or came for delivery in labor room. Results: A total of 100 women (50 before intervention and 50 after intervention) who delivered newborn babies of 0-7 day’s age were selected purposively. Before POCQI intervention out of fifty only eleven (22 %) women breastfed their new born within one hour after birth. After POCQI intervention, out of fifty, thirty-seven women (74%) exclusive breastfed their new born within one hour. Thus, total increase in term of percentage was 54%. CONCLUSION: The study gives evidence for more needs to enhance breastfeeding uptake in AJK. The prevalence of EIBS was low before implementation of POCQI model but it improved significantly after its application